PENGARUH PENAMBAHAN SUKROSA TERHADAP STABILITAS ASETOSAL DALAM DAPAR FOSFAT - ifiet pantilata; suwaldi suwaldi (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2007)
ABSTRACTAsetil salisilat acid or known as acetosal or aspirin is a class of analgetic and antipyretic medicine that used widely. In this research we used acetosal to know it stability for sucrose effect. Acetosal stability examination of temperature effect and pH that done in several sucrose concentration, they are 5,0 %; 10,0 %; and 15,0 % which pH 7,0; 8,0; 9,0 and 10,0 in the 40 0C, 50 0C and 60 0C. The result of research showed that acetosal degradation reaction the sucrose fluid in pH 7,0; 8,0; 9,0 and 10,0 at the 40 0C can speedyacetosal degradation where the speed degradation with sucrose effect has more higher value than the degradation without sucrose effect, while in the 50 0C and 60 0C sucrose made stability of acetosal where degradation value with sucrose effect that smaller than degradation speed without sucrose effect. Key words : asetosal, stability, sucrose